A importância do sistema de controle interno para a eficiência e eficácia da gestão pública municipal, no âmbito do agreste meridional de Pernambuco - Silva, Marcus Antônio Lessa (2011)
This article discuss the importance of implementing the SCI (Sistema de Controle Interno – Internal Control System) in the municipal administration, expressing the need to adopt the practice in the Agreste Meridional (southern dry region) of Pernambuco. This article also highlights that to obtain success using the SCI, it is imperative that all the all legal procedures are followed. This way, the administrator will be in a position to provide and access information; therefore he or she will be able to answer very specific questions, and will have a plentiful and detailed vision of his/her administration. Because of this, it can be said that the implementation of the SCI is a tool that offers the public support, since it provides conditions to manage in an efficient way, by having trustworthy information at one´s fingertips, in a short period of time, respecting government programs and resulting in excellent management conduct. The study also reveals the procedures adopted by municipal administrations since the Resolution nº 001/2009, put in place by the Tribunal de Contas do Estado de Pernambuco, which regulates the creation, implementation, maintenance and coordination of SCIs for municipalities, based on the Articles 31 and 74 of the Brazilian Constitution.